Analysis of the nature and communicative projection of the brands that sponsor the elite clubs of European soccer - Mayorga Escalada, Santiago (2024)
Professional soccer in Europe is a global advertising showcase. This research aimed to analyse the typology and the communicative projection of the brands that are official sponsors of the elite clubs of European professional soccer. The study is conducted through a content analysis of the sponsoring brands of all the first-division clubs of the five European leagues with the highest market value in the 2022/2023 season. This analysis identifies the clubs that have been part of the Champions League. In other words, the elite of European professional soccer. Sponsorship is a strategic action that pursues achieving a series of communication objectives for brands. In conclusion, it is determined that the brands that sponsor the elite European soccer clubs come mainly from Asia, Europe, and America. Their global activity is multinational brands related to the banking, airlines, and digital industry sectors. Their communication interests through sponsorship have to do with positioning, visibility and international reputation. Many of these brands are front companies in strategic governmental sectors that implicitly generate territorial branding for purely reputational communication purposes and to whiten their image in the international context through sport.